Koli woman selling fish - Mumbai Archive Project Team (Jio Institute, 2024)
Koli women purchase fresh catch from fishermen, either directly from the docks or at fish auctions, and sell it in local markets, door-to-door, or to wholesale buyers. Wholesale fish markets play a crucial role in the supply chain, connecting fishermen with retailers, restaurants, and consumers throughout Mumbai and beyond.